Cross-country comparison of competition Rules: institutions and the interface with utility regulation - Rowat, Malcolm (Revista do IBRAC, 2025)
Competition Policy Nexus with Regulated Industries Major Dimensions: 1. Structure - Break-up or unbundling decisions at time of privatization - Mergers and acquisitions - Scope of business restrictions (concession terms) 2. Entry - Defining and reasonably accessing essential facilities 3. Conduct - Pricing - Collusion - Abuse of dominant position